Hydrochemical characterization and numerical simulation of fluid flow in a compressional tectonic environment - Yousafzai, M. Asim (Journal of Himalayan Earth Sciences, 2007)
Groundwater samples were analyzed from springs and wells as part of a larger program of investigations in a compressional tectonic environment. The study site covers the Peshawar Basin and its surroundings in the Himalayan foothills which is experiencing a tectonic compression of 90 Mpa because of the ongoing India - Eurasia collision. The study area extends from Main Karakoram Thrust (MKT) and Main Mantle Thrust (MMT) in the north, through Main Central Thrust (MCT) and Main Boundary Thrust (MBT) in the center to Salt Range Thrust (SRT) in the south. The study area can be divided into two hydrogeological domains. Springs with normal (< 20oC) and anomalously high temperatures (up to 68oC) are abundant in the northern part of the study area while the southern part is divided into isolated basins with a number of drilled wells and dug-wells. Hydrochemical signatures of elevated strontium (Sr), SiO2, boron (B)-and the geothermometric signatures - all indicate a deep circulation of the emerging groundwater. Moreover, for several of the sampling sites, analyzed water compositions, measured spring and water well temperatures, and reservoir temperatures calculated for spring waters, all point to waters that are anomalous in both chemistry and temperature. These characteristics suggest origin of the anomalous waters from deep horizons within the basin. Remarkable proximity of all the thermal and hydrochemical anomalies to major mapped faults suggests that the anomalous waters ascended along these faults from greater depths. The Peshawar intermontane basin is a broad, oval shaped depression comprising of a thick sequence of lacustrine, deltaic and fluvial sediments overlain by loess and alluvial deposits. The basin was divided into four hydrostratigraphic units in order to perform numerical simulations using the 3-D finite-element (FEMWATER) module of Groundwater Modeling System (GMS). Pressure head data generated by the numerical simulations have been compared with the field measurements of hydraulic heads. Results of the transient simulations indicate that topography alone is not sufficient to induce the pressure heads observed in the field, generating consistently positive residuals, ranging 0.98-2.90 m over the topography-driven flow. The positive residuals disappeared after inclusion of the elastic properties of the four hydrostratigraphic units in the model, suggesting the additional effect of tectonic compression on subsurface water flow.